Differences in drug quality between South Africa and Germany. (25th July 2018) - Lehmann, Andreas; Hofsäss, Martin; Dressman, Jennifer
Abstract: Objectives: To examine differences in drug product quality between products marketed in developed countries and in developing countries. Methods: The quality of drug products marketed in both Germany and South Africa by the same pharmaceutical company was compared. A fixed-dose combination tablet containing amoxicillin/clavulanic acid, and mometasone furoate nasal spray were selected to represent generic medicines requiring prescriptions, while skin lightening products (legally obtained and/or confiscated) were selected to represent pharmaceutical products that are available without a prescription. Pharmacopoeial tests included assay, content uniformity, and where applicable, dissolution in addition to a visual examination of the packaging. Key findings: Some differences between the product marketed in Germany and in South Africa were detected for the amoxicillin tablet formulations, although all samples still complied with regulatory requirements. The mometasone nasal spray product marketed in South Africa delivered a higher dose than was declared on the label. The composition of the skin lightening products conformed qualitatively with labelling, but in some South African samples alarmingly high amounts of hydroquinone were found. Conclusions: Important differences in quality were detected between some German and South African products. To preclude drug products of poor or doubtful quality from entering the market in South Africa, countermeasures are needed.